Analysis and Comparison of ESG Strategies and Their Impact on Sustainable Development Goals (SDGs) in the Automotive Industry: A Case Study of Renault and Volkswagen - Bezerra, Luiz Thiago do Sacramento; Santos, Zildomar Carvalho; de Oliveira, Manoel Alcides Caminha Mendes; Moreira, Anderson Luiz Souza; Junior, Paulo Maurício Gonçalves; Oliveira, José Mário Alexandre Melo; Domingues, Marco Antônio de Oliveira; do Carvalho, Fernando Ferreira; Medeiros, Erika Carlos; Lyra, Marília Regina Costa Castro; do Nascimento, Rogéria Mendes (Archives of Business Research, 2024)
This study analyzes and compares the Environmental, Social, and Governance (ESG) strategies adopted by Renault and Volkswagen, focusing on how these practices are integrated into their global operations and their impact on the Sustainable Development Goals (SDGs). Renault and Volkswagen demonstrate significant commitments to reducing CO2 emissions and promoting sustainable practices. Renault focuses on expanding its electric vehicle lineup and improving energy efficiency, while Volkswagen emphasizes the goal of 100% renewable energy usage by 2025. Social initiatives include Renault’s diversity and inclusion programs and Volkswagen’s community development efforts. Both companies maintain strong governance systems to ensure transparency and ethics, aligning with various SDGs. This analysis highlights the different approaches each automaker takes towards achieving sustainability goals, reflecting their specific priorities and contexts within the automotive industry.